Kommunikationstechnische Optimierung eines energieautarken funkbasierten Sensorkonzepts - Senft, Florian (HTWK Leipzig - OA-Hochschulverlag, 2019)
In this bachelor thesis, an existing wireless sensor concept was examined with regard to software optimization possibilities. First, the application possibilities of such sensor systems in the existing maintenance strategies were described. Subsequently, an analysis of the previous sensor concept was carried out, on the basis of which an alternative concept to communication optimisation was realised with the existing hardware. By replacing the previously used application protocol HTTP with the lightweight MQTT, an alternative sensor concept was created. In addition, a measurement concept was developed to determine the transmission time, which allows a comparison with the existing sensor concept. It was thus possible to evaluate the extent to which the objective had been achieved.